2016
DOI: 10.1186/s40729-016-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor and pro-inflammatory cytokine contents in platelet-rich plasma (PRP), plasma rich in growth factors (PRGF), advanced platelet-rich fibrin (A-PRF), and concentrated growth factors (CGF)

Abstract: BackgroundThe development of platelet-rich fibrin (PRF) drastically simplified the preparation procedure of platelet-concentrated biomaterials, such as platelet-rich plasma (PRP), and facilitated their clinical application. PRF’s clinical effectiveness has often been demonstrated in pre-clinical and clinical studies; however, it is still controversial whether growth factors are significantly concentrated in PRF preparations to facilitate wound healing and tissue regeneration. To address this matter, we perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
275
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(317 citation statements)
references
References 20 publications
(19 reference statements)
6
275
1
7
Order By: Relevance
“…16,17 Concentrated growth factors (CGF) were introduced by Sacco as a therapeutic protocol obtained by separation from centrifuged venous blood using a special device in the same manner as PRF. 21 It has been stated that CGF forms rich layers of growth factors including transforming growth factor-beta 1 (TGF-β1), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), insulinlike growth factor (IGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), and bone morphogenic protein (BMP) 20 and deliver these specific growth factors at the site of application. 20 Furthermore, CGF has been found to be almost identical to self-clotted advanced-PRF (A-PRF) in respect of mechanical and degradation properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Concentrated growth factors (CGF) were introduced by Sacco as a therapeutic protocol obtained by separation from centrifuged venous blood using a special device in the same manner as PRF. 21 It has been stated that CGF forms rich layers of growth factors including transforming growth factor-beta 1 (TGF-β1), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), insulinlike growth factor (IGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), and bone morphogenic protein (BMP) 20 and deliver these specific growth factors at the site of application. 20 Furthermore, CGF has been found to be almost identical to self-clotted advanced-PRF (A-PRF) in respect of mechanical and degradation properties.…”
mentioning
confidence: 99%
“…18 While CGF has been stated to be an improved formulation of PRF, 19 it has also been proposed that a different term is used for CGF because of the use of a different centrifuge machine (MEDIFUGE, Silfradent srl, S. Sofia, Italy) and centrifugation speed (2400 to 3000 rpm). 21 Previous studies have indicated that CGF accelerates new bone formation related to guided bone regeneration. 21 It has been stated that CGF forms rich layers of growth factors including transforming growth factor-beta 1 (TGF-β1), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), insulinlike growth factor (IGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), and bone morphogenic protein (BMP) 20 and deliver these specific growth factors at the site of application.…”
mentioning
confidence: 99%
“…Unfortunately, the WBC concentration was not reported for the techniques used for producing PRPs in cattle [11, 12, 29], which prevents us from comparing our findings with those reports.…”
Section: Discussionmentioning
confidence: 73%
“…27, 28, 29 Ehrenfest et al suggested that the various platelet concentrates can be classified into four main categories, depending on the known leukocyte content and fibrin architecture: 30, 31, 32 pure platelet-rich plasma (P-PRP), leukocyte- and platelet-rich plasma (L-PRP), pure platelet-rich fibrin (P-PRF), and leukocyte- and platelet-rich fibrin (L-PRF). Given this variety of preparations and applications of platelet concentrates, 32 studies do not always adhere to the proposed classification, which leads to inconsistent results and confusion in comparing the efficacy of PRP products.…”
Section: Prp Treatment: Preparation and Biological Characteristicsmentioning
confidence: 99%